Pengaruh literasi ekonomi dan pemanfaatan media sosial terhadap minat berwirausaha peserta didik - Irfani Nadia Putri; Norida Canda Sakti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
Entrepreneurship is one of the solutions to reduce the high unemployment that occurs in a country, in order to create a prosperous country, a large number of entrepreneurs are needed. However, in reality, interest in entrepreneurship, especially in students as an easy generation is still relatively low. The purpose of this research is 1) analyze the effect of economic literacy on students' entrepreneurial interest, 2) analyze the effect of social media utilization on students' entrepreneurial interest 3) analyze the effect of economic literacy and social media utilization simultaneously on students' entrepreneurial interest. The research method used is causal associative research with a quantitative approach. The sample in this study were students of class XI IPS SMAN Waru Sidoarjo. The analysis technique used in this research is multiple linear regression analysis using IBM SPSS version 25. The results showed that simultaneously economic literacy variables and social media utilization have an influence on students' entrepreneurial interest with the obtained R2 value of 34%. While partially, the results showed that economic literacy has no significant effect on entrepreneurial interest. Social media utilization has a significant effect on student entrepreneurial interest.